Online users’ donation behavior to medical crowdfunding projects: Mediating analysis of social presence and perceived differences in trust - Zhang, Tao; Zhang, Qianyu; Jiang, Rong; Gao, Tilei; Yang, Ming (Frontiers in Psychology, 2022)
Perceived trust is a key factor affecting the behavior to donate Online. In order to further explore the factors and influencing mechanisms that affect the success of medical crowdfunding projects, this paper, combined with the Stimulus-Organism-Response (S-O-R) theory, introduces the mediating variable of social presence and perceived differences in trust, and constructs a model of online users' donation behavior to medical crowdfunding projects. We collected 437 valid samples through questionnaire survey, and processed the data with SPSS and Amos software to test and analyze the theoretical model. The research results showed that project description and user participation have a significant positive effect on the social presence; project transparency and patient identity have a significant negative effect on perceived differences in trust; social presence has a positive effect on donation behavior, while perceived difference in trust have a negative effect; social presence and perceived differences in trust play a mediating role respectively; there is no significant effect of patient status on social presence. This study further expands the application of social presence and perceived differences in trust in the medical crowdfunding, and provides a theoretical basis for the success of medical crowdfunding projects.